Trust-based load-offloading protocol to reduce service delays in fog-computing-empowered IoT. (July 2021) - Mazumdar, Nabajyoti; Nag, Amitava; Singh, Jyoti Prakash
Abstract: The proliferation of Internet of Things (IoT)-enabled applications such as smart cities, e-healthcare, industrial automation, etc., has resulted in a significant increase in the amount of data produced by these applications. The traditional two-layered cloud-based IoT framework is reported to incur a significant delay in data processing due to the large distance between IoT devices and the cloud server, making them incompatible for time-sensitive applications. A three-layered IoT–fog–cloud framework is proposed to overcome the said limitation and cater to the needs of time-sensitive applications. This paper presents fog nodes collaborative scheme to share the load of the overloaded fog node to ensure timely service. The proposed load-sharing scheme also takes care of the security aspect by developing a trust-based load-offloading method. The efficiency of the proposed model is evaluated via a simulation study to show its effectiveness over the existing methods with latency and service response rate as performance metrics. Graphical abstract: Highlights: A real-time load-balancing scheme with minimum communication overhead among overloaded fog nodes. A trusted load-sharing network created using fog registration centre. Nodes are authenticated with fog registration centre before sharing loads.